2007
DOI: 10.1063/1.2743024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oscillating sheath on near-wall conductivity in Hall thrusters

Abstract: The effect of an oscillating sheath on near-wall conductivity has been studied using a model of the incident electron motions with the characteristic parameters of the oscillating sheath quantified. The model predicted an increase in both the frequency of electron-wall collisions and the coefficient of secondary electron emission compared to the steady sheath regime. This effect indicates that near-wall conductivity is enhanced in the oscillating sheath regime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Meanwhile, as the works in Ref. [9,10,13] found that the surface erosion, oscillating sheath etc. can enhance the NWC effect, so the sheath effect on NWC becomes further weaker.…”
Section: Numerical Modelmentioning
confidence: 97%
See 2 more Smart Citations
“…Meanwhile, as the works in Ref. [9,10,13] found that the surface erosion, oscillating sheath etc. can enhance the NWC effect, so the sheath effect on NWC becomes further weaker.…”
Section: Numerical Modelmentioning
confidence: 97%
“…Under these two NWC models, a current density peak was found near the channel wall. Later, these two models were subjected to many modifications and the results showed that NWC is infruenced by many factors, such as surface erosion, magnetic field gradient in radial direction, plasma wall recombination and oscillating sheath, etc [9][10][11][12][13]. All the previous models on NWC only considered that the magnetic field is perpendicular to the wall.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…As addressed in Ref. [13], Δφ d is close to the corresponding steady-state Debye jump Δφ d , A doesn't exceed the magnitude of Δφ d , and f sh is equal to the electron plasma frequency of the near-wall region. In view that the plasma parameters those determine the electron plasma frequency have a non-uniform distribution along the thruster channel and given the various frequency bands of plasma instabilities from a general point of view, we extend the oscillation frequency to a considerable wide range for obtaining a comprehensive knowledge.…”
Section: Secondary Electron Motion Modelmentioning
confidence: 95%
“…Hall thruster simulations reveal sheath instabilities that abruptly alter the state of the plasma [9] and drive oscillations [10,11]. Sheath oscillations may considerably increase near-wall conductivity in HT's [10,12] and cause interference [13]. However, the precise causes and conditions for sheath instability are not yet quantified.…”
mentioning
confidence: 99%